THE EFFECT OF THE TEAM GAMES TOURNAMENT (TGT) COOPERATIVE LEARNING MODEL ON EIGHTH-GRADE STUDENTS' LEARNING OUTCOMES IN LIGHT TOPIC - Rini Kurnia Putri; Khairil Arif; Tuti Lestari; Rani Oktavia (Universe, 2026)
ABSTRACT   Students' low learning outcomes in science are often associated with instructional approaches that provide limited opportunities for active participation and collaborative learning. The Team Games Tournament (TGT) cooperative learning model has been widely recognized as an effective strategy for promoting student engagement and improving academic achievement. This study aimed to examine the effect of the TGT cooperative learning model on eighth-grade students' learning outcomes in the topic of light. A quasi-experimental research design employing a nonequivalent pretest–posttest control group design was used. The participants were selected through purposive sampling from seventh-grade classes at a public junior high school, with 25 students assigned to the experimental group and 25 students to the control group. Data were analyzed using an independent-samples t-test. The results revealed a statistically significant difference in learning outcomes between the experimental and control groups (p = 0.022 < 0.05), indicating that students who learned through the TGT cooperative learning model achieved significantly better learning outcomes than those who received conventional instruction. These findings demonstrate that the TGT cooperative learning model is an effective instructional approach for improving eighth-grade students' learning outcomes in the topic of light.